2021
DOI: 10.1016/j.eclinm.2021.100988
|View full text |Cite
|
Sign up to set email alerts
|

High cerebrospinal amyloid-β 42 is associated with normal cognition in individuals with brain amyloidosis

Abstract: Background Brain amyloidosis does not invariably predict dementia. We hypothesized that high soluble 42-amino acid β amyloid (Aβ42) peptide levels are associated with normal cognition and hippocampal volume despite increasing brain amyloidosis. Methods This cross-sectional study of 598 amyloid-positive participants in the Alzheimer's Disease Neuroimaging Initiative cohort examined whether levels of soluble Aβ42 are higher in amyloid-positive normal cognition (NC) indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 31 publications
(47 reference statements)
7
51
0
Order By: Relevance
“…Table 8 presents values of the biomarkers total tau, tau phosphorylated at threonine 181 (p-tau 181 ), and amyloid β 1–42 as measured in CSF at baseline and the number of patients carrying the apolipoprotein ε4 allele (APOE4) gene according to ADCOMS staging groups. People staged as having normal cognition using the ADCOMS have significantly lower mean tau and p-tau 181 levels and significantly higher mean amyloid β 1–42 values than those staged as having early AD (soluble amyloid β 1–42 is known to decrease as patients progress[ 21 ]). Additionally, the likelihood of being an APOE4 carrier increased across the ADCOMS staging groups, such that people staged as having moderate/severe AD had the highest likelihood of carrying this gene.…”
Section: Resultsmentioning
confidence: 99%
“…Table 8 presents values of the biomarkers total tau, tau phosphorylated at threonine 181 (p-tau 181 ), and amyloid β 1–42 as measured in CSF at baseline and the number of patients carrying the apolipoprotein ε4 allele (APOE4) gene according to ADCOMS staging groups. People staged as having normal cognition using the ADCOMS have significantly lower mean tau and p-tau 181 levels and significantly higher mean amyloid β 1–42 values than those staged as having early AD (soluble amyloid β 1–42 is known to decrease as patients progress[ 21 ]). Additionally, the likelihood of being an APOE4 carrier increased across the ADCOMS staging groups, such that people staged as having moderate/severe AD had the highest likelihood of carrying this gene.…”
Section: Resultsmentioning
confidence: 99%
“…The role of amyloid plaque in Alzheimer's disease is undecided with accumulating evidence indicating that it might not be the pathogenic trigger driving the neurodegenerative cascade (e.g. Sturchio et al, 2021). Alternative explanatory mechanisms that trigger and interact with known antecedents to neurodegenerative pathology are thus needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite both drugs demonstrated convincing Aβ target engagement, gantenerumab failed to show a beneficial effect on cognitive measures, whereas solanezumab-treated group even exhibited a greater cognitive decline on some measures compared to placebo [9]. One week later, a cross sectional study conducted on 598 amyloid-positive participants patients was published and revealed that soluble Aβ 42 levels above 800 pg/ml were correlated with normal cognition irrespective of (and despite increasing) brain amyloid burden, implying that increasing soluble Aβ 42 , rather than reducing Aβ plaques, might represent a better therapeutic option [11]. We believe that these evidences should be taken into account for the future regulatory decision-making.…”
Section: Discussionmentioning
confidence: 99%